From Religiosity to Representing Cultural Identity: Communication Approach in the Changes of Indonesia's Halal policy on Instagram - Mualimin, Mualimin; Saliro, Sri Sudono; Yunaldi, Ari; Muhammad, Rifqi (Journal of Southeast Asian Islam and Society, 2025)
The article aims to emphasize the communication approach of the Indonesian halal certification authority on Instagram in explaining halal policy changes, including the halal logo change and the halal certification authority. The article’s method is qualitative, with a content analysis approach. Data was collected by observing the official Instagram accounts of the Indonesian Ministry of Religious Affairs and the Halal Product Guarantee Agency (BPJPH). The posts observed were from March to December 2022. The data obtained were then analyzed using the Miles and Huberman interactive qualitative analysis model: data display, data reduction, and conclusion. The study found that public communication implemented by the Ministry of Religious Affairs and the Halal Product Guarantee Agency (BPJPH) on Instagram is aimed at convincing the public of the arguments for changing the halal logo and the authority of halal certification in Indonesia. The design and rhetoric of posts are aimed at building narratives and arguments that the new halal logo is more representative of Indonesian identity than the previous logo. The narration is also built to convince the public that the change in the authority to issue halal certificates to the Halal Product Guarantee Agency (BPJPH) is not to eliminate the role of the Indonesian Ulama Council but to make its role and function more explicit in halal certification. The study also found that the Halal Product Guarantee Agency (BPJPH) posted positive testimonials from influential public figures exposed to changes in logos and halal certification policies in Indonesia. These testimonials are used to legitimize arguments and narrations to gain public acceptance, approval, and trust.